Dalea extracts as potential ingredients for phyto-formulations: Antioxidant, antityrosinase, antifungal and cytotoxicity in vitro evaluations - del Gaudio, Micaela Paula (2020)
Dalea L. (Fabaceae) includes species used in traditional medicine. Prenylflavonoids from Dalea, such as 2’,4’-dihydroxy-5’-(1’’’,1’’’-dimethylallyl)-8-prenylpinocembrin (8PP) present antioxidant,antityrosinase, and antifungal activities. This work aimed to investigate the chemical and biological properties of Dalea leporina, a species without any chemical or biological study, and to compare it with D. boliviana and D. pazensis.Hydro-alcoholic extracts from roots of the three species were obtained and their antioxidant,antityrosinase, antifungal, and cytotoxicity activities were evaluated, together with total phenols and flavonoids quantification and evaluation of relative content of 8PP in the threeextracts.D. boliviana presented the highest polyphenolics and flavonoid contents and antioxidant properties.8PP was determined in the three Dalea extracts, with the highest content in D. pazensis, which showed relevant tyrosinase inhibition. D. leporina showed important antifungal activity againstazole-resistant Candida albicans. Dalea extracts showed important bioactivities and high maximum non-cytotoxic concentrations, and are potential sources of new phyto-bioactive ingredients.